Asas Legalitas Dan Self Plagiarism: Antinomi Realitas Empiris Sebagai Proyeksi Pengaturan Tindak Pidana Khusus Di Bidang Hak Cipta - Hardiago, David; Syafrinaldi (UIR Press, 2022)
This study aims to analyze and provide projections in order to answer the problem of self-plagiarism in relation to positive legal regulations in Indonesia which regulate copyright. As a normative legal research, this study uses several approaches including the statute approach, conceptual approach, and comparative approach. The results of the study conclude that the current act of self-plagiarism is completely unknown in positive law regulations in Indonesia, especially in regulations related to copyright. The absence of these regulations has an impact on the absence of sanctions for acts of self-plagiarism, both ethical sanctions and criminal sanctions. While it is known that self-plagiarism has a greater detrimental impact when compared to pragmatic plagiarism and is known in positive laws and regulations with ethical and criminal sanctions that can be applied. Thus, with the empirical reality of self-plagiarism it is projected that the act in question is regulated as a crime in the copyright regulations that will be formed in the future by providing and including criminal threats against acts of self-plagiarism in the form of a total reformulation of the current regulations.